CASE REPORT: UNILATERAL CONJUNGTIVITIS AND WIDENING OF NIKTITAN MEMBRANE IN LOCAL CAT - Dewi, Dyah Utami; Suartha, I Nyoman; Soma, I Gede (Buletin Veteriner Udayana; Vol. 14 No. 4 August 2022DO - 10.24843/bulvet.2022.v14.i04.p13, 2022)
A local male cat has ± 1.5 years old with a body weight of 2.9 kg, experiencing interference with the right eye since September 2019 and has been treated. Clinical examination shows the absence of pupillary reflexes on the right eye. The examination was continued using an ophthalmoscope in which the pupil of the right eye was not visible, and a fluorescent test was also performed with the result that no ulcer was found in the cornea of ??the eye. There is a widening of the niktitan membrane in the right eye which causes the pupil to be invisible and almost covers the entire eye so that the examination is not optimal. The niktitan membrane was dilated, thought to be due to friction when the cat scratched its eye. The results of routine hematological examination showed that cats had leukocytosis and lymphocytosis. Case cats are diagnosed with conjunctivitis due to bacterial infection. Treatment given to cats diagnosed as having conjunctivitis is given therapy with Doxycycline (PO: 14.5 mg / kg BW), Dexamethasone (PO: 0.5 mg / kg BW), Oxytetracycline HCl 1% (R/ Oxytetra 1% opth ointment tube) dan Chlorampenicol (R/ Erlamycetin eye drops). After 7 (seven) days of treatment the clinical signs of the eye showed insignificant improvement in the widening of the membrane, but the inflammation of the conjunctiva had begun to improve.